Faktor yang Mempengaruhi Perilaku Konsumsi Alkohol Anak Jalanan di Kota Kediri - Esta Ruri Solecha; Diah Indriani (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2017)
The behavior of alcohol consumption among street children is a serious health problem, because the behavior can have a negative impact. This behavior occurs due to imperfect social interaction in the community and life within the family of street children. This study aims to determine the factors that influence the behavior of alcohol consumption in street children in Kediri. This research method using quantitative approach method. The population in this study is all street children in Kediri with the criteria of adolescents ie age 10-19 years. The sample used in this study were 30 respondents, using accidental sampling method. The variables used are alcohol consumption behavior, attitude, knowledge, affordability, and peers. Data were collected using questionnaire and data analysis using Chi-square test. The results showed that of 30 street children respondents 76.7% consumed alcohol. The result of Chi-square test shows that the level factor of knowledge, attitude, affordability and environment of peers who have many opportunities to perform alcohol consumption behavior is the affordability factor with OR = 15.8. This means that the easier a person to get an alcoholic drink the greater the chance to behave alcohol consumption.